Effect of microwave treatment on the structural and functional properties of proteins in lentil flour. (October 2022) - Mahalaxmi, S.; Himashree, P.; Malini, B.; Sunil, C.K.
Highlights: Lentils were MW treated and then defatted to investigate its impact. Functional and thermal properties, FTIR, SEM and X-ray diffraction were studied. MW treatment improved the functional and thermal properties. Structural changes were observed in the MW treated samples. MW treatment altered the crystalline and amorphous nature of the lentil flour. Abstract: Microwave is the commonly adopted thermal technology for the cooking and other industrial processing of lentils. The study focused on evaluating the effect of microwave treatment (MT) on the protein profile and functional properties of lentil flour (LF). The lentils with 18% moisture content were exposed to MT at three different power levels (540, 720, and 900 W) and exposure times (2, 4, and 6 min). The treated lentil flour samples were defatted before further studies. The results revealed that the MT positively impacted most of the desired functional properties like water and oil absorption capacity and emulsion properties; also, MT has an insignificant effect on foaming capacity, and significantly reduced the foaming stability from 80.25% to 60%. The structure of the MT flours differed from the untreated counterparts, and MT improved the functional properties of lentil flour. Protein secondary structural changes were observed in MT flour. It was observed that MT altered the crystalline and amorphous natures of the LF, implying that MT is appealing as an alternative emerging technology to improve the functional and quality parameters of lentil proteins with potential applications for other pulse proteins. Graphical Abstract: Image, graphical abstract .